Diagnóstico de sistemas de proteção coletiva em canteiros de obras na região de São Carlos - Santos, Camila Rodrigues Ferreira Guimarães (2013)
In the context of the construction industry today, it is noted that there are a lot of accidents at work, making it thus very dangerous. In order to minimize the consequences of these accidents occurred and the quantities we seek to develop with this study the diagnostic use of Collective Protection Systems (CPS) used in the construction sites in the region of São Carlos focusing in more depth in the system guardrail and footer and platforms protection. Through a network of collaborative research It was elaborated a checklist, based on the normative references have been studied mainly in NR 18 - Conditions and working environment in the construction industry, to evaluate the use of CPS at construction sites. In order to improve the checklist developed was applied in a pilot study and, based on the results obtained, we could make suggestions for improvement. Then began the case studies belonging to the region of São Carlos contemplating nine construction sites. The case studies spread to close cities in the region, as Ribeirão Preto, Jaboticabal and Limeira. After application of the list in the eight sites, we elaborated a list summary and from there, was analyzed the data using photographic records and graphics. The average percentage care of the checklist was 79%, thus showing that many normative items were met, but there is a percentage to improvement of sites in the study region. Finally, after diagnosis the use of CPS drew up guidelines for the choice and use of CPS specific system guardrail and footer and protection platform. Furthermore, it was noted that the lack of use or incorrect use of the CPS at construction sites, often does not occur by technological problems, but by failures in administrative directives or inspection existing in the industry.